Pre-Service EFL Teachers and Faculty Members' Views on the Challenges and Complexities of Online Research Supervision amid COVID-19 - Pardede, Parlindungan; Purnamasari, Asri (JET (Journal of English Teaching), 2021)
Undergraduate research supervision has long been one of the most intricate learning issues due to its complexities and challenges. The policy to learn from home during COVID 19 pandemic could have increased the complexities and challenges. This study aimed at discovering the nature of problems and challenges of undergraduate research supervision in the English Education Department of Universitas Kristen Indonesia Jakarta, Indonesia. Employing a qualitative method using a content analysis approach, this study was conducted in October to November 2020 involving 5 faculty members and 15 students who participated in the research supervision held amid COVID 19. Data from the faculty members were gathered through a questionnaire and semi-structured interviews, and data from the students were gathered using a questionnaire and focus group discussions. The obtained data were analyzed using the qualitative content analysis technique. The results revealed that the students viewed the online undergraduate supervision during COVID as very complex and challenging due to their limited research and writing skills, inability to access the research fields, inadequate ICT skills for research, absence of face-to-face communication, and ICT constraints. Both supervisees and supervisors generally viewed the online research supervision was more complex and challenging than the traditional face-to-face research supervision.